Imagination - (:unkn) unknown (My University, 2025)
This theoretical project aims at understanding the dynamics of imagination from a sociocultural psychology perspective. Involving various collaborations and secondary analysis of diverse data, it has so far brought to modelise the loop of imagination, understood as individual and collective dynamic, and its outcomes in terms of problem solving, development, and social change. It also aims to examine imagination in the lifecourse, as well as resources and constraints for imagining. Further issues involve the relations between imagination and learning, remembering, creativity, etc.
Keywords: Imagination; sociocultural psychology; semiotic processes; theory